Beban Kerja Perempuan sebagai Kondektur Bus Taruna Jurusan Semarang-Solo - Fierza Ainda Prawesti; Suyanto Suyanto; Retna Hanani (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The existence of sosial transformation makes women being able to access in public domain for work. However, the equality that has slowly been achieved created a new problem, namely double burden borne by women because they are required to take responsibility on all their household chores. This study aims to describe the double burden borne by women bus conductor workers. This type of research is qualitative with descriptive methods with data collection techniques through observation, in-depth interviews and documentation. The results showed that the double burden of women conductors was related to the physical workload of taking care of the household and working as a bus codector as well as the psychological burden which in their work environment they often get less wearing behavior in the form of catcall. Working women conductors are able to help meet the economic needs of their families, on the one hand they bear a heavy burden in their work and complain about fatigue and aches as a result of their work. There is a negative view due to double burden they run. Less time for gathering with family because they spent a lot of it in working. To face the double burden they experience, working women divide their time to do all the work they have to do.